Bayt al-Hikmah: A Prototype of the Classical Islamic Library and a Model for Modern Islamic Digital Libraries - Parangu, Reza Nawafella Alya (Universitas Islam Negeri Raden Intan Lampung, 2025)
This article examines Bayt al-Hikmah as a prototype of the scientific library in classical Islamic civilization by highlighting its institutional characteristics and its relevance for the development of contemporary Islamic digital libraries. The study employs a qualitative method with a historical-institutional analytical approach through library research, drawing on primary sources such as al-Fihrist and secondary literature in Islamic history and library science using thematic content analysis. The findings indicate that Bayt al-Hikmah functioned not only as a translation center but also as a research institution, a library, and a cross-cultural scholarly forum that integrated the production, preservation, and dissemination of knowledge. Librarians played significant roles in cataloguing, transliteration, and manuscript conservation, which, from a modern perspective, reflect early forms of knowledge management and the functions of knowledge brokers. The study further identifies institutional features such as openness, multidisciplinarity, and state-supported scholarly collaboration as key elements shaping the intellectual legacy of Bayt al-Hikmah. The research concludes that Bayt al-Hikmah represents an early knowledge ecosystem whose principles remain highly relevant for the development of Islamic digital libraries, particularly in the areas of open access, digital preservation, and information management.